Changes in HbA1c and Weight Following Transition to Continuous Subcutaneous Insulin Infusion Therapy in Adults With Type 1 Diabetes. (January 2017) - Mehta, Sanjeev N.; Andersen, Henrik Ullits; Abrahamson, Martin J.; Wolpert, Howard A.; Hommel, Eva E.; McMullen, William; Ridderstråle, Martin
Background: Historically, intensive insulin therapy for type 1 diabetes (T1D) has improved glycemic control at the risk of adverse weight gain. The impact of continuous subcutaneous insulin infusion therapy (CSII) on weight in the current era remains unknown. We assessed changes in hemoglobin A1c (HbA1c) and weight in adults with T1D transitioning to CSII at 2 diabetes centers in Denmark and the United States. Methods: Patients with T1D, aged ≥18 years, managed with multiple daily injections (MDI) who transitioned to CSII between 2002 and 2013 were identified using electronic health record data from the Steno Diabetes Center (n = 600) and Joslin Diabetes Center (n = 658). Changes in HbA1c and weight after 1 year was assessed overall and by baseline HbA1c cut points. Multivariate regression assessed correlates of HbA1c reduction. Results: In adults with T1D transitioning to CSII, clinically significant HbA1c reductions were found in patients with baseline HbA1c 8.0-8.9% (Steno, –0.7%; Joslin, –0.4%) and baseline HbA1c ≥9.0% (Steno, –1.1%; Joslin, –0.9%) ( P < .005 for all). Overall, there was no significant change in weight after 1 year at either center. Modest (<2%) weight gain was noted in patients with baseline HbA1c ≥9% at Steno (1.1 ± 0.3 kg, P < .0001) and Joslin (1.7 ± 1.1, P < .005). In multivariate models, HbA1c reduction was associated with higher HbA1c, older age, female sex at Steno ( R 2 = .28, P < .005), but only higher baseline HbA1c at Joslin ( R 2 = .19, P < .005). Conclusion: Adults with T1D with suboptimal glycemic control significantly improved HbA1c without a negative impact on weight 1 year after transitioning from MDI to CSII.